PENGARUH KOMPETENSI, INDEPENDENSI DAN INTEGRITAS AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA PADANG - Sari, Mutiara; Arza, Fefri Indra; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACTResearch purposes is to get picture of influence competence, pendency and integrity auditor the quality of the audit office on public accountant padang.The type of research used in this research is quantitative approach with korelasional Research aims to uncover the relationship competencies Auditor, Auditor Independence and the integrity of the Auditors of the quality Audit. The research was carried out on a public accountant Padang city that was implemented in October 2013 until January 2014. The population of the research was the Auditor of public accountant in Padang city consists of 7 (seven) public accountant (KAP) and the number of Auditors as many as 80 people as research samples. Research instrument using a questionnaire that diadobsi from previous research with Likert scale models, analyzed with simple correlation and multiple regression.The research met: (1) the value t tabel 1,669 and value tcount from to three variable free large of the value ttable i.e. tcount competence auditor 6,675Inpendency auditor 2,025 and tcount integrity auditor 6,965 of data are known tcount bigger than ttable; (2) results analisi test simultaneous f (f) obtained table of 2,476 and value f hitung of 30,348, (3) the magnitude of determination (R2) or percentage donations competence, pendency, and itegritas auditor betawi together the quality of the audit of 58,3 %, and (4) results the regression equation is double is & amp; Å¶=1,390 + 0,367 X1 + 0,102 X2 + 0,356 X3.Based on the results of data analysis can researchers conclude that: (1) Competence significantly influence the quality of the audit on public accountant Padang city, (2) the independence of the influential significantly to quality audits on public accountant Padang city, (3) the integrity of the influential significantly to quality audits on public accountant Padang city, and (4) the competence, Independence and integrity of the Auditors are jointly contributing significantly to the quality of the audit on public accountant Padang city.Â